Experimental evaluation of an active fault–tolerant control method. (October 2015) - Schuh, M.; Zgorzelski, M.; Lunze, J.
Abstract: A method for the active fault–tolerant control of systems modeled by deterministic input/output (I/O) automata is presented and evaluated experimentally. In the fault-free case, a given controller moves the system into a specified final state. The aim of the paper is to construct a framework which guarantees that the final state is reached again after the occurrence of a fault. In this paper, two existing methods, one for the fault diagnosis and one for the reconfiguration of I/O automata, are combined in order to obtain an active and completely autonomous FTC framework. It is shown how the developed method can be applied to a handling system and that it indeed makes the faulty system again fulfill its given task.